A brief overview on Brazilian women in chemistry - Santos, Natacha Carvalho Ferreira; Valli, Marilia [UNESP]; Da Silva Bolzani, Vanderlan [UNESP] (De Gruyter, 2019)
Women have achieved great advances standing up for themselves in the last 100 years. Many important women were essential for the development of science but only a few (5% from total awarded individuals) have won Nobel prizes for their work. In this brief contribution, we would like to show that gender equality is in process and highlight the gaps that still have to be addressed. We also give an overview of the Brazilian scenario on this matter. In many countries, such as Brazil, women are already half of the researchers in Chemistry, but their representation become scarcer as their career advances, in coordination and direction positions.
Keywords: Brazil; chemistry; Distinguished Women in Chemistry and Chemical Engineering; science; women